The Nepotism as a Main Form of Corruption - et al., Ali Mukartono (International Journal of Advanced Science and Technology, 2019)
Nepotism is any act of a State Administrator contradictory to the law which benefits his/her family and or cronies, disregarding the interests of society, the nation and the state. With the support of power, the practice of nepotism can be a fertile land that can produce corruption that is truly abundant. This article provides an overview of how the practice of nepotism began to be known in the world, including its development in Indonesia, especially in the New Order era. This article also describes the eradication of corruption by applying the nepotism offence as the main form of corruption, will be able to avoid greater state losses due to this crime. The application of this nepotism offense can be used as a strategy to eradicate corruption that is not only in the form of repressive but also as a means to prevent corruption.